Pengaruh Nasi Aron Khas Suku Tengger Terhadap Perubahan Kadar Glukosa Darah 2 Jam Post-Prandial - Biasnurbani, Intan Kinanti; Mayasari, Noor Rohmah (Media Gizi Kesmas, 2025)
Background: In 2021, Indonesia recorded 19.5 million cases of diabetes mellitus. Women exhibit a 1.02 fold higher risk of developing diabetes mellitus when accounting for physical factors. Dietary management using the special concept (schedule, amount, and type) is an appropriate choice for diabetes mellitus patients to control blood glucose levels. Aron rice, a processed white corn variety typical of the Tengger tribe, is high in fiber and may help control blood glucose levels. Objectives: This objective of this research is to examine the effect of Tengger tribe's special Aron rice on 2-hour post-prandial blood glucose levels in healthy adult women. Methods: This experimental method involved interventions with control food (pure sugar) and test food (Aron rice). The research design used a pre-test post-test one-group design. The sample consisted of 16 participants selected through purposive sampling based on inclusion criteria. The study was carried out from July to September 2024. The instruments in this study utilized the observation method of 2-hour post-prandial blood glucose measurements following the administration of control and test foods. The data were analyzed using a paired t-test to examine the effect of Aron rice on changes in 2-hour post-prandial blood glucose levels. Results: The study findings indicate an average blood glucose level before the control food was 87.75 mg/dL, while before the test food, it was 85.88 mg/dL, with a p-value of 0.107>0.05, indicating no significant difference in fasting blood glucose levels at minute 0. After the control food, the average blood glucose level was 115.63 mg/dL, while after the test food, it was 90.00 mg/dL. There was a mean difference of 25.63 mg/dL with a p-value of 0.000<0.05, indicating a significant difference in fasting blood glucose levels in 2 hours. Conclusion: Tengger tribe's special Aron rice affects changes on 2-hour post-prandial blood glucose levels in healthy adult women, resulting in lower levels compared to pure sugar. Aron rice can be an alternative staple food for diabetes mellitus patients as an effort to improve blood glucose control in the body.